2022
DOI: 10.3390/genes13122338
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of CYP4D2 Putatively Associated with β-Cypermethrin Detoxification in Phortica okadai

Abstract: Phortica okadai, a polyphagous pest, serves as a vector for Thelazia callipaeda in China. Currently, there are no effective control strategies for this vector. Agricultural pest control may cause P. okadai to become a threat due to the development of pesticide resistance. Cytochrome P450s (CYP450) plays a significant role in detoxifying xenobiotics in insects. In this study, we performed RNA sequencing of P. okadai exposed to β-cypermethrin for 0 and 1 h and then gene cloning of the five up-regulated CYP450 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…According to tissue expression profiles of Tribolium castaneum , TcCYP6BQ8 is mostly expressed in the head and integument of both larvae and adults [ 53 ]. In another research, Pocyp4d2 had the highest expression in the midgut of Phortica okadai [ 54 ]. It was reported that SsubCYP341A and SsubCYP341B_ortholog1 were more highly expressed in the pheromone gland than in the female body of Scopula subpunctaria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to tissue expression profiles of Tribolium castaneum , TcCYP6BQ8 is mostly expressed in the head and integument of both larvae and adults [ 53 ]. In another research, Pocyp4d2 had the highest expression in the midgut of Phortica okadai [ 54 ]. It was reported that SsubCYP341A and SsubCYP341B_ortholog1 were more highly expressed in the pheromone gland than in the female body of Scopula subpunctaria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%